Gender, experimenter gender and medium of report influence the content of autobiographical memory report. Issue 1 (2nd January 2017) - Grysman, Azriel; Denney, Amelia
ABSTRACT: In this study, we examined the role of context in autobiographical memory narratives, specifically as it pertains to gender among emerging adults. Male and female participants reported stressful events in their lives in the presence of an experimenter, and were randomly assigned either to report events verbally or type them, and to report in the presence of a male or female experimenter. Narratives were coded for factual and interpretive content. Results revealed that men verbally reporting to women reported longer narratives than all other groups. Women's narrative length did not vary by medium of report or conversational partner, but women used proportionally fewer internal state phrases when verbally reporting to men than when reporting to women. Women also used proportionally fewer evaluative statements in verbal reports than in typed narratives. Of these important interactions among context, gender, and experimenter gender, some findings, such as men's longer narratives and women's reduced internal states, were counter to expectations. These findings highlight the importance of methodological influences in autobiographical memory studies, in regard to both the context generated by experimental methods, and how gender differences are understood.